Pengaruh E-Govqual Terhadap Kepuasan Peserta Pada Layanan Klaim Jaminan Hari Tua (JHT) di BPJS Ketenagakerjaan Rokan Hulu Riau - Aditia, Aditia; Simanjuntak, Harapan Tua Ricky Fredy; Othman, Lie (Ministrate: Jurnal Birokrasi dan Pemerintahan Daerah, 2023)
This research is motivated by the existence of the concept of Electronic -Government Quality (E-Govqual) which is urgently needed to be implemented in public organizations to improve the quality of public services through the use of information technology. The purpose of this study was to find out and analyze how E-Govqual influences participant satisfaction in the Old Age Guarantee Claim (JHT) service at BPJS Ketenagakerjaan Rokan Hulu Riau. This study uses a quantitative method, using smart PLS. The population of this study were all participants who submitted JHT claims at the Rokan Hulu Riau Employment BPJS, the total sample being 189 respondents. Data collection techniques using questionnaires. there are 24 attributes in this study which are grouped into 4 Variables (X) Efficiency, Trust, Reliability and Employee Support and 1 Variable (Y) Participant Satisfaction. The results of the study show that there is a positive effect of E-Govqual on participant satisfaction in the JHT claim service at the Rokan Hulu Employment BPJS.